Human Brain Organoid Models of Developmental Epilepsies. Issue 5 (September 2020) - Nieto-Estévez, Vanesa; Hsieh, Jenny
Epilepsy is a common neurological disorder characterized by recurrent and unprovoked seizures due to neuronal hyperactivity. A large proportion of epilepsy cases begin during childhood. Causes of epilepsy include stroke, infections, brain injury, genetic factors, or other factors that alter brain structure and development, but in up to 50% of cases the cause is unknown. Approximately 35% of patients have refractory seizures that do not respond to medication. Animal models and in vitro cultures have contributed to our understanding of epilepsy, but there is a clear need for better models to explore the human brain in normal and pathological conditions. Human pluripotent stem cell (PSC) technologies opened the door for new models for analyzing brain development and disease, especially conditions with a genetic component. Initially, PSCs were differentiated into 2-dimensional cultures of a homogenous population of neural cells, such as glutamatergic excitatory or γ-aminobutyric acidergic inhibitory neurons, as well as glial cells. Nevertheless, these cultures lacked the structure and complexity of a human brain. In the last decade, PSC technology has advanced to the next level through the development of 3-dimensional culture, called organoids. These organoids recapitulate features of the human brain that are missing in animal models, enabling a deeper study of the human brain. In this review, we will summarize the current status of organoid research and its application to epilepsy.